Controversies, consensuses and guidelines on posterior chamber phakic intraocular lens for the correction of myopia and myopic astigmatism in healthy phakic eyes by the Academy of Asia-Pacific Professors of Ophthalmology (AAPPO) and the Asia-Pacific Myopia Society (APMS) - Lai, Kenny H.W.; Wang, Xiao Ying; Wan, Kelvin H.; Barsam, Allon; Barnes, Scott D.; Chiu, Alison L.S.; Cummings, Arthur B.; Eldanasoury, Alaa M.; Huang, Guofu; Kamiya, Kazutaka; Leyssens, Barbara; Li, Shi-Ming; et al. (Asia-Pacific journal of ophthalmology (Philadelphia, Pa.), 2025)
Phakic Intraocular Lens (pIOL) has been studied for correction of high myopia and myopic astigmatism long before the advent of laser refractive surgery. It offers excellent visual and refractive outcomes, but the inherited risk of intraocular surgery cannot be overlooked. The posterior chamber pIOL (PC-pIOL), designed to be placed in the ciliary sulcus, may offer additional advantages compared to its anterior chamber counterparts. Given the complexity of sulcus anatomy and individual variations, controversies exist regarding perioperative management, implant selection, and operative techniques, necessitating standardisation. Given the emergence of novel approaches and long-term clinical data, a panel comprising 19 international experts from 9 countries/territories was formed by the Academy of Asia-Pacific Professors of Ophthalmology (AAPPO) and the Asia-Pacific Myopia Society (APMS). The panel critically reviewed the subject and synthesised 58 consensus statements that aim to provide evidence-based, real-world practice recommendations for optimal outcomes in PC-pIOL surgery.